Eksplorasi Implementasi Good Governance dalam Perencanaan Pembangunan Desa di Desa Patemon Kecamatan Pakusari Kabupaten Jember - Hanip, Muhammad; Kristianto, Adil; Khoirurizka, Meynisa Aulia; Nanda, Destha Bunga; Kusumaningrum, Adelia; Yudhistira, Prillinaya; Ardhiarisca, Oryza (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
Good governance is the key to successful village development in achieving community welfare. This study examines the implementation of good governance principles in development planning of Patemon Village, Pakusari District, Jember Regency, focusing on accountability, transparency, and community participation. Using a descriptive qualitative approach, this study collected data through in-depth interviews with the Village Secretary and active community members. Data analysis employed Miles and Huberman technique. The results reveal that Patemon Village has implemented good governance mechanisms in a structured manner, yet faces significant challenges. Accountability operates through routine reporting to the Inspectorate, but accessibility to detailed information for the community remains limited. Transparency is manifested through village deliberations and budget banners, but the information is general with limited reach. Community participation is conducted through tiered deliberations, but remains unequal with priority misalignments due to budget constraints. This study recommends developing a more accessible reporting system, optimizing information technology for transparency, strengthening inclusive participation mechanisms, enhancing village officials' capacity, and implementing impact-oriented supervision to strengthen effective and participatory village governance.